Sketch [videorecording (Blu-Ray + DVD)] - Fry, Cody, 1990- (Angel Studios, 2025)
When a young girl's sketchbook falls into a strange pond, her drawings come to life--unpredictable, chaotic, and dangerously real. As the town unravels, she and her brother must track down the creatures before they leave permanent damage. Their father, racing to find them through the fallout, must navigate a town in crisis to reunite his family and stop the disaster they never meant to unleash.